Peran Video Editor Dalam Produksi Program Kampungku (Studi Deskriptif di TVRI Sumsel) - Panesa Selvia; Sumaina Duku; Jawasi Jawasi (Social Science and Contemporary Issues Journal, 2024)
ABSTRACT: The "Kampungku" program is one of the flagship programs aired by this television station, which aims to raise the potential and life of rural communities in South Sumatra. This research aims to reveal the role played by video editors in the production of the "Kampungku" program at TVRI South Sumatra. In addition, this research also seeks an understanding of the editing techniques applied by video editors in the context of the production of the "Kampungku" program. The research method used is a descriptive qualitative approach by conducting direct observation, in-depth interviews, and content analysis of the video production process involved in the "Kampungku" program. The data collected was then analyzed using the Miles and Huberman data analysis technique which involves three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the role of video editors in the production of the "Kampungku" program at TVRI South Sumatra has great significance. They are responsible for editing the video content which includes clip selection, story sequencing, audio adjustments, and visual effects utilization. In addition, video editors also have an important role in maintaining the consistency of the program's visual and narrative style in accordance with TVRI South Sumatera's production standards. As such, this research provides an in-depth understanding of the important contribution of video editors in structuring and producing the program.